Disfungsi Peradilan Pajak Indonesia dalam Merealisasikan Keadilan - Handika, Irine (Jurnal Hukum dan Peradilan, 2012)
Appeals is a remedy that can be used by the taxpayers during the tax dispute with the tax authorities, having previously filed Objection. Philosophy of remedies is a means of seeking justice to fight for their rights as equal before the law, it should be an option that gives freedom for the taxpayer to use or not use. Anomaly occurs, where the Act Number 28 of 2007 on General Provisions and Tax Procedures seeking justice requires to pay the administrative sanction a fine of 100% of Appeals were denied or granted in part. In the middle of the threat of sanctions, taxpayers are dealing with a lower ability of court to produce a fair Judgment for the parties. Therefore, the realization of the Tax Judiciary functions as a conduit of Fairness should be questioned and examined. Keywords: Appeal, Objection, Fine, Judiciary, Fairness